Digital Learning Transformation: The Impact of a Learning Management System-Based E-Book on Classical Assumption Tests in Statistics Courses - Hari Sugiharto Setyaedhi; Atan Pramana (Jurnal Edutech Undiksha, 2024)
The development of e-books specifically for Statistics courses, particularly regarding classical assumption tests, remains limited. This condition negatively impacts students' learning interest, ultimately affecting their academic performance. This study aims to develop and assess the feasibility of a Learning Management System (LMS)-based e-book on classical assumption tests to provide students with flexible access through the VineSA platform. The research employs a development method using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects include material experts, media experts, instructional design experts, language experts, and 90 students. Data collection techniques involve observation, interviews, questionnaires, and tests. Data were analyzed using descriptive qualitative and quantitative methods. The validation results indicate that the LMS-based e-book on classical assumption tests is highly feasible for use, with the following scores: material validation at 91% (highly feasible), media validation at 90% (highly feasible), instructional design validation at 94% (highly feasible), language validation at 90% (highly feasible), individual trials at 80% (highly feasible), and small group trials at 83% (highly feasible). The study concludes that the LMS-based e-book is feasible to be used as teaching material and can improve students' academic performance.